Cognitive Test Differences Between our Bronx English and Spanish Speaking Patients: Lessons Learned Through the Expansion of Neuropsychological Services. (30th August 2019) - Weiss, E; Facchini, R; Zwerling, J
Abstract: Objective: To demonstrate the differences between the English-speaking and Spanish-speaking patients evaluated at a Memory Disorders Clinic. Participants and Method: Through a foundation grant to reduce barriers to appropriate neurological care, we established a bilingual/bicultural neuropsychology post-doctoral fellowship. In the initial 2 years, 405 new patients were seen at our multidisciplinary memory disorders clinics for neuropsychological and neurological evaluations. These patients were 63% female (n = 256), and had a mean age of 73.09 (SD = 10.63, range 52-98). Fifty-eight percent of our population identified as Hispanic/Latino (primarily Puerto Rican and Dominican) and 42% were evaluated in Spanish. Results: Patients evaluated in Spanish had less education (p < .001) and were younger (p = .03) than those evaluated in English (including our Hispanic/Latino English speaking patients). Individuals evaluated in Spanish performed worse on a mental status exam (Blessed) than those evaluated in English (p = .001) even after controlling for age and education (p = .048). However, those evaluated in Spanish were more likely to do better on memory tasks than those evaluated in English, compared to their respective normative peers. Higher levels of anxiety and depression were evident in Hispanics/Latinos compared to non-Hispanics with highest levels in Hispanics evaluated in English. Conclusions: Through a grant to expand services to the previously underserved Spanish-only speaking population of the Bronx, we were able to validate the need for appropriate language and cultural resources in our robust medical community. We demonstrated that our Spanish speaking population is diverse and requires different resources from their English-speaking counterparts. Our data supports the establishment of additional studies (including improved cultural and language specific normative data) and further education of providers working with our diverse populations.